If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + x = -4 + -1x Solving 4 + x = -4 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 4 + x + x = -4 + -1x + x Combine like terms: x + x = 2x 4 + 2x = -4 + -1x + x Combine like terms: -1x + x = 0 4 + 2x = -4 + 0 4 + 2x = -4 Add '-4' to each side of the equation. 4 + -4 + 2x = -4 + -4 Combine like terms: 4 + -4 = 0 0 + 2x = -4 + -4 2x = -4 + -4 Combine like terms: -4 + -4 = -8 2x = -8 Divide each side by '2'. x = -4 Simplifying x = -4
| 3(4d+1)-9d=6(-2m+5)-4 | | x-(2x+3)=-4 | | 2x^3+7x^2-7x-30=0 | | 2w+2(6w-6)= | | 5+3x=5x+7 | | 60=4(6r+3) | | Z-4.3=1.6 | | x+(3x+11)=3 | | (11x-1)+(5y-5)=180 | | -12x+8y=-12 | | -22x+9x= | | 8.3z=4.1z+10.2 | | 0.128-0.035v=0.072v+0.235 | | 6x-x=3x+30 | | 15=5d-5 | | 44-(-b)=76 | | 5x-3+7-8x=19 | | (T)=t^2+100t | | 5z+2=3iz+4i | | wx+b=yforx | | 6c-8=4c | | x+2=-6+72 | | 8x-2=x+4 | | v^2=37 | | 4-9=-13 | | f(x)=0.6+2.75 | | 2a-1=18 | | 4=m/7+5 | | 5n=-3n | | v^3=37 | | 4(x-4)+8=12 | | 2(x+4)+3=15 |